PERMASALAHAN ASPEK FORMIL PENYELESAIAN SENGKETA PEMBATALAN PENETAPAN CALON ANGGOTA DPR DAN DPRD KABUPATEN/KOTA/PROVINSI TERPILIH - Muhammad Adiguna Bimasakti (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2021)
Law No. 7 of 2017 concerning General Elections (General Elections Act) stipulates that the General Election Commission (KPU) has the authority to determine the elected participants in the Election of Candidates of members of the House of Representative and/or the Regency/City/Provincial House of Representative. The General Elections Act also regulates how the process of resolving disputes over the election process and disputes over election results. However, in the event of cancellation or change in the Decision regarding the elected Candidates of members of the House of Representative and/or the Regency/City/Provincial House of Representative by KPU, in the event of a dispute, General Election Act doesn't regulate the dispute resolution process. Thus, this paper tries to explain this problem. The writing method used in this research is a legal-normative approach using statutory approach and conceptual approach. The results of the study indicate that KPU has the authority to resolve disputes over the cancellation or change in the Decision regarding the elected Candidates of members of the House of Representative and/or the Regency/City/Provincial House of Representative according to Law no. 30 of 2014 concerning Government Administration, namely through administrative proceedings in the form of administrative objection even though the General Election Act doesn't regulate it, then proceed to an administrative appeal to the KPU's superior. The Administrative Court is also authorized to adjudicate the dispute as an administrative dispute as regulated in the laws and regulations related to the procedural law of the administrative court.